2023
DOI: 10.1128/aac.00328-23
|View full text |Cite
|
Sign up to set email alerts
|

A Clinically Selected Staphylococcus aureus clpP Mutant Survives Daptomycin Treatment by Reducing Binding of the Antibiotic and Adapting a Rod-Shaped Morphology

Abstract: Daptomycin is a last-resort antibiotic used for the treatment of infections caused by Gram-positive antibiotic-resistant bacteria, such as methicillin-resistant Staphylococcus aureus (MRSA). Treatment failure is commonly linked to accumulation of point mutations; however, the contribution of single mutations to resistance and the mechanisms underlying resistance remain incompletely understood. Here, we show that a single nucleotide polymorphism (SNP) selected during daptomycin therapy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…In a few cases, accumulation of Spx has been experimentally verified in clinical MRSA strains that developed resistance during treatment (50). The clinical relevance of Spx stabilization for S. aureus survival during antibiotic treatment is further supported by the selection of mutations that inactivate the YjbH-ClpXP protease in S. aureus isolates from patients undergoing treatment with β-lactams, daptomycin or vancomycin (4245, 51). Moreover, a comprehensive genetic study identified the yjbH gene as a hot spot for adaptive mutations during infections supporting that S. aureus may benefit from high Spx levels in clinical settings, but the role of antibiotics in selection was not discussed in this study (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a few cases, accumulation of Spx has been experimentally verified in clinical MRSA strains that developed resistance during treatment (50). The clinical relevance of Spx stabilization for S. aureus survival during antibiotic treatment is further supported by the selection of mutations that inactivate the YjbH-ClpXP protease in S. aureus isolates from patients undergoing treatment with β-lactams, daptomycin or vancomycin (4245, 51). Moreover, a comprehensive genetic study identified the yjbH gene as a hot spot for adaptive mutations during infections supporting that S. aureus may benefit from high Spx levels in clinical settings, but the role of antibiotics in selection was not discussed in this study (28).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations that inactivate the YjbH-ClpXP protease complex responsible for Spx degradation have on several occasions been identified in clinical strains that developed resistance to these antibiotics during treatment (42)(43)(44)(45). This prompted us to investigate if inactivation of yjbH or depletion of Spx would impact growth of S. aureus in the presence of these critical antibiotics.…”
Section: High Spx Broadly Potentiates Resistance To Compounds Targeti...mentioning
confidence: 99%
“…The blue-shaded cells identify mutations that have been previously observed in laboratory and clinical isolates. [14][15][16][17][18][19][20][21][22][23][24][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] We list the affected genes along the bottom in order of the total number of mutations.…”
Section: Genomic Analysis Reveals Mutations and Pathways In Vancomyci...mentioning
confidence: 99%